Modeling Air Pollutant Dispersion in Urban Areas: A HYSPLIT-Based Analysis of PM 2.5 Dynamics in Medan, Indonesia - Mustaqiman, Aulia Nur; Tia Dwi Irawandani; Wisnu Prayogo; Sapta Suhardono (Jurnal Serambi Engineering, 2025)
Air pollution is a critical environmental challenge in urban areas, particularly developing regions like Medan, Indonesia. This study aims to analyze the dynamics of PM 2.5 dispersion, identify pollution sources, and assess the role of meteorological factors in influencing air quality. Using the HYSPLIT model, the research examines pollutant transport and dispersion over ten months, specifically focusing on a high-pollution episode in May 2024. The study integrates meteorological data and local air quality measurements to simulate forward and backward trajectories at multiple altitudes. The results reveal that PM 2.5 concentrations in Medan are driven by local emissions, such as transportation and industrial activities, and transboundary pollution from biomass burning in neighboring provinces. Higher altitudes capture the influence of regional winds, while localized sources and atmospheric turbulence dominate near-surface levels. Meteorological conditions, including wind patterns, temperature stability, and rainfall, significantly affect pollutant dispersion and accumulation. By leveraging advanced modeling tools and meteorological data, the study provides a robust framework for air quality management in urban environments. These insights contribute to the broader understanding of pollution dynamics and support evidence-based strategies to protect public health and the environment.